If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2.5x Solving 0 = 2.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5x' to each side of the equation. 0 + -2.5x = 2.5x + -2.5x Remove the zero: -2.5x = 2.5x + -2.5x Combine like terms: 2.5x + -2.5x = 0.0 -2.5x = 0.0 Divide each side by '-2.5'. x = 0 Simplifying x = 0
| 3x+10=5(2x+2)-2x | | .13=3.14r^2 | | 5a-11b+11b-6a= | | (4lnx)-1/3lny | | 0=2-2y+x | | y=x^3+8x^2+21x+15 | | Bx=-1 | | 4/3x-7=7/3 | | (x+5)12=144 | | 7x^2-7=x^3-x | | 3r=r^2 | | 4m-4-8=-2+12 | | 10=(1+8y)5 | | 109=-4(5x-1)-x | | 14u^2-6u+21u-9= | | 64y=y^3 | | -59+3x=9x+103 | | 3x-10=4x-14 | | 5x+10-3x+17-16+12x=28 | | 5/9(-9) | | 2(4x-1)-3=2x+4 | | 0.6(25x+35)=0.33(30+45x) | | 2(4x-1)-3=2+x+4 | | 4(5u+4)=3[-4u+4(-u-6)] | | U+4=-7 | | 10-6(2x^2)=60 | | 2x+3y+4z=32 | | 9(t-1)/6t | | 35s^2-10s+21s-6= | | 7+-16=6+-16 | | 2(4x-1)-3=4+x+-2 | | 6x^2-60x+148=148 |